Effect of several amines on the morphology, structure, purity, and photocatalytic activity of Ni6MnO8 nanostructures - Masoumeh Yaqoubi; Masoud Salavati-Niasari; Mojgan Ghanbari (Applied Water Science)
Abstract Water and wastewater contaminated by dyes are becoming a bigger global problem. The drawbacks of conventional treatment methods are their high prices, lack of sustainability, and partial elimination. Metal oxide semiconductor-based photocatalytic degradation has lately supplanted these techniques. One method promising for completely degrading azo dyes found in wastewater is photocatalysis. Ni6MnO8 nanostructures, a novel photocatalyst, were created in this study to aid in the photocatalytic breakdown of several dyes, especially Eriochrome Black T (EBT). These nanostructures were fabricated through a simple and low-cost co-precipitation method using different amines, including ammonia, tetraethylenepentamine, triethylenetetramine, and ethylenediamine (EDA) as precipitating and capping agents. The pure phase of Ni6MnO8 was achieved in the presence of ammonia. According to the DRS result (bandgap = 2.6 eV), visible light was used to conduct photocatalytic degradation tests on a several dyes solution. The results show that the degradation is greatly influenced by the type of catalyst, dye solution’s starting concentration, pH of dye solution, and the amount of catalyst used. Increased catalyst dose and acidic media result in increased degradation. The maximum degradation rate of Ni6MnO8 prepared in the presence of ammonia on EBT is 96.3% under visible light, and its pseudo-first-order reaction rate constant is 0.0182 min–1. The scavenger experiment revealed the hydroxyl radicals performed the superior role in the degradation of EBT. The recycling test indicated the high stability of Ni6MnO8, with the yield reduced by only 5.6% after five cycles.